If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 3 = 9 + -9y + 18 Reorder the terms: 3 + 3y = 9 + -9y + 18 Reorder the terms: 3 + 3y = 9 + 18 + -9y Combine like terms: 9 + 18 = 27 3 + 3y = 27 + -9y Solving 3 + 3y = 27 + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. 3 + 3y + 9y = 27 + -9y + 9y Combine like terms: 3y + 9y = 12y 3 + 12y = 27 + -9y + 9y Combine like terms: -9y + 9y = 0 3 + 12y = 27 + 0 3 + 12y = 27 Add '-3' to each side of the equation. 3 + -3 + 12y = 27 + -3 Combine like terms: 3 + -3 = 0 0 + 12y = 27 + -3 12y = 27 + -3 Combine like terms: 27 + -3 = 24 12y = 24 Divide each side by '12'. y = 2 Simplifying y = 2
| -(5x+12)=18 | | 7(4.3+x)= | | 2x+3=12x+8 | | 1/4(8d-4)=d+8-2d | | 3(x)-5(13)= | | 4(7x+7)=28x+28 | | 17(n+18)=612 | | 5(a-2)=2(10+a) | | -4+6(-4x+3)= | | 4y^2-45=0 | | -2(-8(-1)+2)=4(2(-1)-3) | | 3(h-4)=-1/2(24-6h) | | 4y*.8-.1=3y+.8 | | 4y*.8-.1=3*.8+.8 | | 9x^4-y^2=0 | | -16t^2+112+288= | | -3-4(x-5)=-2(x+3)+11 | | x/4=45 | | x^2-4=11 | | -2(-8p+2)=4(2p-3) | | -2(-3k+4)-7= | | 5z-5=4z+16 | | 5y+4=2y+9 | | -14x-1.8=-24x+3.9 | | 90+9x=7(x+30) | | 3x+5=9x | | 9+16x^2=0 | | 4x+7-2x=3+5x-6 | | -n+4(n+1)= | | 9(4998)= | | -49/7=a+7/6 | | -8(5-3v)= |